2017
DOI: 10.3390/catal7080232
|View full text |Cite
|
Sign up to set email alerts
|

Functionalization of SSZ-13 and Fe-Beta with Copper by NH3 and NO Facilitated Solid-State Ion-Exchange

Abstract: Abstract:We show that functionalization of SSZ-13 (CHA) and Fe-beta (*BEA) with copper using a recently reported solid-state ion-exchange method, facilitated by NH 3 and nitrogen oxides (NO), is a viable route to prepare Cu-SSZ-13 and (Cu + Fe)-beta catalysts, starting from H-SSZ-13 and Fe-beta, respectively. The physicochemical properties of the prepared catalysts are characterized by XRD, UV-Vis-spectroscopy and STEM-EDS, confirming that copper originally present in the physical mixture of CuO and H-SSZ-13, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 27 publications
(46 reference statements)
1
12
0
Order By: Relevance
“…Despite different reaction conditions, the SCR-NH3 performance of combined (2%)Cu-(2%)Fe-BEA catalyst prepared by solid ion-exchange method ([NH3+NO] SSIE) [14] is similar to our results. Contrary to the results obtained by using the dual-layer samples [10], the activity of the studied mechanical mixture is not decreased by diffusion limitation.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…Despite different reaction conditions, the SCR-NH3 performance of combined (2%)Cu-(2%)Fe-BEA catalyst prepared by solid ion-exchange method ([NH3+NO] SSIE) [14] is similar to our results. Contrary to the results obtained by using the dual-layer samples [10], the activity of the studied mechanical mixture is not decreased by diffusion limitation.…”
Section: Discussionsupporting
confidence: 88%
“…This suggests a synergistic effect between Cu and Fe metals in the mixed catalysts resulting in higher SCR-NH3 (when NOx/NH3 = 1.3) in a wider temperature range. In addition, it was recently shown that the copper of CuO species becomes mobile in the presence of NH3 and NO at medium temperatures (250-350 °C), resulting in the migration of Cu species [14,39]. Based on this feature, several composite (Cu+Fe)-zeolite catalysts were prepared starting from the physical mixture of CuO and Fe-exchanged zeolites under NO and NH3 [39].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Among the most attractive exhaust aftertreatment techniques for lean NO x reduction is the selective catalytic reduction with either ammonia (NH 3 -SCR) or hydrocarbons (HC-SCR). For example, Cu-based zeolites have recently been shown to exhibit high NO x removal activity in a wide temperature range [1][2][3]. In contrast to NH 3 -SCR, the HC-SCR catalysts need to be further improved as to be competitive.…”
Section: Introductionmentioning
confidence: 99%